A Retrospective Observational Study to Determine Baseline Characteristics and Early Prescribing Patterns for Patients Receiving Alirocumab in UK Clinical Practice - Tim Reynolds; Peter Carey; Jacob George; Gerasimos Konidaris; Deepa Narayanan; Sudarshan Ramachandran; Luke Saunders; Adie Viljoen; Gordon Ferns (Adis, Springer Healthcare, 2019)
Abstract Background Alirocumab is a fully human monoclonal antibody to proprotein convertase subtilisin/kexin type 9 (PCSK9) and has been previously shown, in the phase III ODYSSEY clinical trial program, to provide significant lowering of low-density lipoprotein cholesterol (LDL-C) and reduction in risk of major adverse cardiovascular events. However, real-world evidence to date is limited. Objective The primary objective was to describe baseline characteristics, clinical history, and prior lipid-lowering therapy (LLT) use of patients initiated on alirocumab in UK clinical practice following publication of health technology appraisal (HTA) body recommendations. Secondary objectives included description of alirocumab use and lipid parameter outcomes over a 4-month follow-up period. Methods In this retrospective, single-arm, observational, multicenter study, data were collected for 150 patients initiated on alirocumab. Results Mean (standard deviation; SD) age of patients was 61.4 (10.5) years and baseline median (interquartile range; IQR) LDL-C level was 4.8 (4.2-5.8) mmol/l. Alirocumab use occurred predominantly in patients with heterozygous familial hypercholesterolemia (HeFH) (n = 100/150, 66%) and those with statin intolerance (n = 123/150, 82%). Most patients started on alirocumab 75 mg (n = 108/150 [72%]) and 35 (23.3%) were up-titrated to 150 mg. Clinically significant reductions in atherogenic lipid parameters were observed with alirocumab, including LDL-C (median [IQR] change from baseline, − 53.6% [− 62.9 to − 34.9], P < 0.001). Conclusion This study highlights the unmet need for additional LLT in patients with uncontrolled hyperlipidemia and demonstrates the clinical utility of alirocumab in early real-world practice, where dosing flexibility is an important attribute of this therapeutic option.